Pengaruh Asimetri Informasi, Strategi Diversifikasi dan Leverage terhadap Manajemen Laba - Listya Ningrum; Eka Yulianto (International Forum of Researchers and Lecturers, 2026)
This study aims to examine the effect of information asymmetry, diversification strategy, and leverage on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Earnings management refers to managerial actions that utilize the flexibility of accounting standards to influence reported earnings in financial statements. This research employs a quantitative approach using secondary data obtained from the annual financial reports of listed companies. The sample was selected using a purposive sampling method, resulting in 46 manufacturing companies that met the research criteria, with a total of 230 firm-year observations. Data were analyzed using panel data regression to investigate the relationship between the independent variables and earnings management.The results indicate that information asymmetry has a positive and significant effect on earnings management. This finding suggests that a greater information gap between managers and investors increases the opportunity for managers to engage in earnings management practices. Leverage is also found to have a positive and significant effect on earnings management, indicating that companies with higher debt levels tend to manage earnings to meet contractual obligations and maintain a favorable image among creditors. In contrast, diversification strategy does not have a significant effect on earnings management, implying that operational complexity resulting from diversification does not necessarily encourage earnings manipulation. These findings provide valuable insights for investors, creditors, and regulators in assessing the quality and reliability of corporate financial reporting.